DEVELOPING SUSTAINABLE ISLAMIC BOARDING SCHOOLS: ANALYSIS OF ONE PESANTREN ONE PRODUCT PROGRAM IN FOSTERING SELF-SUFFICIENCY - Nurhasanah, Elis; Saeful Mubarok, Acep Zoni; Az Zahra, Qiny Shonia; Rahmat, Biki Zulfikri (Penamas, 2024)
The “One Pesantren One Product” (“OPOP”) program is a West Java provincial program that has become an initiative in building Islamic boarding school self-sufficiency through economic empowerment by assisting Islamic boarding schools in choosing marketable commodities, providing training, and mentoring. This study aims to analyze the OPOP program's effectiveness in fostering self-sufficiency as a form of sustainable development in Tasikmalaya. Using a qualitative approach that includes case studies and in-depth analysis, this research identifies the significance of the realization of the OPOP program on the self-sufficiency of Islamic boarding schools in Tasikmalaya who recipients of OPOP stimulant funds are. The research examines how the program has facilitated improvements in the economic aspects of Islamic boarding school self-sufficiency. The results show that the OPOP program is able to encourage the financial independence of the OPOP recipient pesantren in the scale-up category by optimizing business productivity, expansion, and networking of pesantren product marketing, which leads to an increase in pesantren income. This explains that the OPOP program can support the successful development of sustainable Islamic boarding schools, especially in financial independence.